Implementation of E Office Applications at Universitas Negeri Malang (UM) - Choirul Anam (Universitas Negeri Surabaya, 2023)
E-office refers to activities in the workplace that utilize electronic equipment and internet networks. At UM, e- office refers to a website-based application that is in the Sistem Informasi Akademik (Siakad). This paper intends to discuss the implementation of e-office applications in UM, the obstacles and challenges of implementation, as well as strategies for maximizing. The research method used is descriptive qualitative. Obtained data through observation, interviews, and literature studies. The results are the e-office at UM has a main function and a secondary function. The main function of the e-office is to write letters and send mail. The secondary function is media filing management, where users can search for certain letters by typing certain words in the Search menu. The obstacle is there are still many academicians, especially students who do not know the existence, even the function of e-office. The solution is socialization and workshops on the use of e-office applications. Maximization that can be done to improve the application in terms of correspondence is a variation of sentence templates and types of letters. The next optimization in filing management is the addition of the feature of scanning a document using a laptop camera, web camera, or cellphone, so the users can easily enter digital files into the e-office database. The second feature to improve records management is setting a record retention schedule.